2018
DOI: 10.20344/amp.8859
|View full text |Cite
|
Sign up to set email alerts
|

Escala de Avaliação da Doença de Alzheimer - Subescala Cognitiva (ADAS-Cog): Dados Normativos para a População Portuguesa

Abstract: RESUMOIntrodução: A Escala de Avaliação da Doença de Alzheimer -subescala cognitiva (ADAS-Cog) é uma bateria neuropsicológica breve desenvolvida para caracterizar o desempenho cognitivo de doentes com doença de Alzheimer. Avalia as funções tipicamente mais comprometidas na doença de Alzheimer considerando os seguintes domínios cognitivos: memória, orientação, linguagem, praxia e capacidade construtiva. A deteção precoce das alterações cognitivas assim como a sua monitorização são fundamentais para a prática em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Interestingly, similar difficulties were also observed in the Brazilian population [23]. The mean score of ADAS-Cog for the Filipino population in this study was 9.98 (SD 4.74; Table 2) compared to 5.6 (SD 3.3) in the USA and 6.12 (SD 2.46) in Portugal [22, 24]. Although the US study population was highly educated (years of schooling 14.8 ± 3.3) and half of the Portuguese study population only had primary education, ADAS-Cog scores were not found to be affected by education in these studies.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, similar difficulties were also observed in the Brazilian population [23]. The mean score of ADAS-Cog for the Filipino population in this study was 9.98 (SD 4.74; Table 2) compared to 5.6 (SD 3.3) in the USA and 6.12 (SD 2.46) in Portugal [22, 24]. Although the US study population was highly educated (years of schooling 14.8 ± 3.3) and half of the Portuguese study population only had primary education, ADAS-Cog scores were not found to be affected by education in these studies.…”
Section: Discussionsupporting
confidence: 81%
“…To date, numerous preclinical studies have suggested a function of CaMK2A in spatial learning and memory (Matsuo et al, 2009; Moriguchi et al, 2014), which is a proposed functional endophenotype of AD (Nogueira et al, 2018). In addition, associations between several variants of CaMK2A and AD have been investigated in other ethnic populations.…”
Section: Discussionmentioning
confidence: 99%
“…These items prove valuable not only in differentiating AD patients from healthy individuals but also in determining disease severity, particularly through the orientation section. 25 Furthermore, it is important to distinguish between MCI and dementia. MCI represents a transitional stage between dementia and the age-related cognitive decline associated with normal aging, with amnestic and non-amnestic subtypes.…”
Section: Discussionmentioning
confidence: 99%